ASUHAN KEBIDANAN PADA NY. N USIA 30 TAHUN, G1,PO, AO USIA KEHAMILAN 28 MINGGU DENGAN HIPERTENSI KRONIK DI KLINIK BERTHA TAHUN 2018 - R. Oktaviance S (Elisabeth Health Jurnal, 2019)
According to the World Health Organization (WHO) in 2008 the number of cases of hypertension there are 839 jutsa cases. This case is estimated to be even higher in 2025 with 1.15 billion cases or about 29% of the total world population. Globally, 80% of deaths are categorized directly in the cause of maternal mortality, which is caused by the occurrence of bleeding (25%), usually postpartum hemorrhage, hypertension in pregnant women (12%), misfiring (8%), abortion (13%) , and for other reasons (7%) (Basana, et al 2017) Objective: To conduct a foster care assessment on ny.N with chronic hypertension using varney obstetric care management. Methods: The type of research is descriptive, with case study methods that aim to see the differences and similarities between theory and pratek about chronic hypertension. Results: The results of midwifery care given to ny.N with chronic hypertension were given in accordance with theoretical care for the treatment of pregnant women with chronic hypertension and in the implementation of upbringing performed until partially resolved problems. Having done penkes and collaboration with doctors in the provision of drug therapy. Conclusion: The care given can not solve the problem of chronic hypertension where from 7 chronic hypertension care handling only 3 theory which is done that is giving therapy drug, health education diet pattern, and do referral with doctor of obstetric specialist to action immediately.